Internet Marketing and Structural Changes e-Commerce in Ukraine - Kolodynskyi, S.; Hutsaliuk, O.; Kramskyi, S.; Zakharchenko, O. (Економічний вісник Донбасу, 2022)
Abstract. The article reveals the essence of Internet marketing as a universal scientific and methodological tool and a complex system of information technologies, which are extremely necessary for the functioning of modern business entities in markets with different structures and dynamics of development. The structure of Ukraine's economy is under the influence of complex global economic relations, and there is an acute problem of applying universal information technologies to determine the direction of the country's development, its inclusion in a complex system of trade relations on world markets, and to withstand competition with global trading companies. Under such difficult conditions, both internal and external, the role of Internet marketing in strengthening, first of all, trade interaction between the regions of the country for the further exit of domestic product manufacturers to world markets is growing sharply.
Purpose and tasks. The purpose of the article is to determine the main components of the influence of Internet marketing on modern commercial processes in the national economy and to establish structural changes in the field of trade in various goods on the national market of Ukraine. Electronic commerce is gaining widespread use in the world and is becoming a cornerstone in the formation of global economic ties between the countries of the world, to which Ukraine is also advancing. However, a number of difficulties on this path become an obstacle to the commercialization of economic relations between domestic enterprises and advanced countries of the world.
Materials and methods. All theoretical conclusions and results of the article are based on the scientific methods of researching the processes of digitalization of economic opportunities, which were based on the provisions of classical economic theory, modern theories of the development of scientific and technological progress. The research methodology is based on the principles of a systematic approach to the analysis of the essence of Internet marketing and the process of restructuring trade relations using the Internet, analysis of the role and place of electronic commercial activity in modern national economic systems, which are transformative and structurally deformed systems based on Internet technologies. In the course of the study, logical, empirical methods of learning the mechanisms and forms of e-commerce management were used, as well as methods of comparative, factorial, situational, economic and statistical analysis, forecasting of the restructuring process, grapho-analytical and algorithmic methods of displaying the obtained research results, software methods and modern information and computer technologies. Priorities in the use of this or that method were determined by the tasks and the purpose of scientific research.
The results. The conducted research reflected the complexity and difficulty of the processes of spreading digital technologies in the economic environment of Ukrainian enterprises. Digitization as a technology characteristic of modern high-tech enterprises affects all spheres of their activity, especially the sphere of commercialization of the results of enterprise activity. The implementation of the product produced and offered for use covers a large number of Ukrainian enterprises and they need the development of Internet marketing, which gives significant advantages to enterprises in the markets. Such advantages include the processes of creating permanent groups of consumers, forming focus groups of consumers, reducing the costs of promoting goods to consumers, using advertising as a tool for forming needs and providing many other advantages, which are indicated in the article. An important result of the conducted research was the analysis of the state and directions of Internet marketing development in the modern Ukrainian economy. The article indicates the main directions of the formation of electronic commerce and the influence of Internet marketing on this process.
Conclusions. The result of the article is an assessment of the economic efficiency of Internet marketing at the current stage of the structural deformation of e-commerce in Ukraine. The increase in the volume and dynamics of electronic trade shows the importance of this type of activity for Ukrainian enterprises and strengthens the global economic ties between the enterprises of our country and the commercial enterprises of the leading countries of the world. Актуальність. У статті розкривається сутність інтернет-маркетингу, як універсального науково-методологічного засобу та складної системи інформаційних технологій які вкрай необхідні для функціонування сучасних суб’єктів господарювання на різних за своєю структурою та динамікою розвитку ринках. Структура господарства України знаходиться під впливом складних світогосподарських зв'язків і виникає гостра проблема застосувати універсальні інформаційні технології для визначення напрямків розвитку країни, включення її в складну систему торгівельних відносин на світових ринках, витримати конкуренцію зі світовими торгівельними компаніями. За таких складних умов, як внутрішніх, так і зовнішніх, різко зростає роль інтернет-маркетингу у посиленні в першу чергу торгівельної взаємодії між регіонами країни для подальшого виходу вітчизняних товаровиробників на світові ринки.
Мета та завдання. Метою статті є визначення головних складових впливу інтернет-маркетингу на сучасні комерційні процеси в національній економіці та встановлення структурних зрушень в галузі торгівлі різноманітними товарами на національному ринку України. Електронна комерція набуває широкого поширення у світі та стає наріжним камінням у формуванні світогосподарських зв'язків між країнами світу до яких просувається і Україна. Однак ряд труднощів на цьому шляху стають перешкодою щодо комерціалізації господарських стосунків між вітчизняними підприємствами та передовими країнами світу.
Матеріали та методи. Всі теоретичні висновки і результати статті ґрунтуються на наукових методах дослідження процесів цифровізації економічних відносин, які базувалися на положеннях класичної економічної теорії, сучасних новітніх теоріях розвитку науково-технічного прогресу. Методологія дослідження ґрунтується на принципах системного підходу до аналізу сутності інтернет-маркетингу та процесу реструктуризації торгівельних відносин за допомогою інтернету, аналізу ролі та місця електронної комерційної діяльності у сучасних національних економічних системах, що є системами трансформаційними та структурно деформованими на засадах інтернет-технологій. У ході дослідження використовувалися логічні, емпіричні методи пізнання механізмів та форм управління електронною комерцією, а також методи порівняльного, факторного, ситуаційного, економіко-статистичного аналізу, прогнозування процесу реструктуризації, графоаналітичних та алгоритмічних методів відображення отриманих результатів дослідження, програмні методи та сучасні інформаційно-комп'ютерні технології. Пріоритети у використанні того чи іншого методу визначалися поставленими завданнями і метою наукового дослідження.
Результати. Проведене дослідження відобразило складність та трудність процесів розповсюдження цифрових технологій в економічному середовищі українських підприємств. Цифровізація як технологія, що характерна для сучасних високотехнологічних підприємств торкається усіх сфер їх діяльності, особливо сфери комерціалізації результатів діяльності підприємств. Реалізація виробленого та запропонованого для вжитку продукту охоплює велику кількість українських підприємств і вони потребують розвитку інтернет-маркетингу, який дає суттєві переваги підприємствам на ринках. До таких переваг відносяться процеси створення постійних груп споживачів, формування фокус-груп споживачів, зменшувати витрати на просування товарів до споживачів, застосовувати рекламу, як інструмент формування потреб та надає багато інших переваг, про які вказано у статті. Важливим результатом проведеного дослідження став аналіз стану та напрямків розвитку інтернет-маркетингу в сучасній українській економіці. В статті вказані основні напрямки формування електронної комерції та вплив на цей процес інтернет-маркетингу.
Висновки. Результатом статі є оцінка економічної ефективності інтернет-маркетингу на сучасному етапі структурної деформації е-комерції в Україні. Зростання обсягів та динаміка електронної торгівлі свідчить про вагомість такого виду діяльності для українських підприємств та посилює світогосподарські зв'язки підприємств нашої країни з комерційними підприємствами передових країн світу.